Accès aux ressources documentaires en situation d'autonomie : pratiques et représentations - Christine Develotte (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In some countries, the incorporation of the Internet into the socio-cultural practices of students is such that on-line documents are used alongside traditional written documents. Language classrooms also benefit from this diversity of educational supports that allow students to work autonomously. However, the information gathering and learning processes employed differ greatly according to the supports used. The values that students attach to these mediums vary greatly. We propose a methodology which will illustrate the practices of advanced French language learners. Using this protocol we will present the results of a study which was undertaken in 2001 with the students of the university of Sydney, Australia.